2007
DOI: 10.1038/sj.emboj.7601928
|View full text |Cite
|
Sign up to set email alerts
|

CBF-1 promotes transcriptional silencing during the establishment of HIV-1 latency

Abstract: The establishment of HIV proviral latency requires the creation of repressive chromatin structures that impair the initiation of transcription and restrict RNAP II elongation. We have found that C‐promoter binding factor‐1 (CBF‐1), a CSL (CBF‐1, Su(H) and Lag‐1)‐type transcription factor and key effector of the Notch signaling pathway, is a remarkably potent and specific inhibitor of the HIV‐1 LTR promoter. Knockdown of endogenous CBF‐1 using specific small hairpin RNAs expressed on lentiviral vectors results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
236
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(251 citation statements)
references
References 51 publications
15
236
0
Order By: Relevance
“…For example, LSF binds YY1 which recruits transcriptional corepressor HDAC1, thus maintaining the transcriptional latency (12). However, other transcription factors binding to the adjacent regions of Nuc-1, such as AP-4 (14), p50 homodimers (13), C-promoter binding factor-1 (15), and Sp1-cMyc complex (16), are known to recruit HDAC proteins leading to transcriptional silencing. Upon stimulation of cells such as by TNF-␣, transcriptional activators including NF-B are recruited together with coactivators exhibiting histone acetyltransferase (HAT) activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, LSF binds YY1 which recruits transcriptional corepressor HDAC1, thus maintaining the transcriptional latency (12). However, other transcription factors binding to the adjacent regions of Nuc-1, such as AP-4 (14), p50 homodimers (13), C-promoter binding factor-1 (15), and Sp1-cMyc complex (16), are known to recruit HDAC proteins leading to transcriptional silencing. Upon stimulation of cells such as by TNF-␣, transcriptional activators including NF-B are recruited together with coactivators exhibiting histone acetyltransferase (HAT) activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to productively infected cells, latently infected cells harboring HIV-1 genomes integrated into heterochromatin structures that allow persistence of transcriptionally silent proviruses (9,10). Hyperacetylation of core histone proteins adjacent to the HIV-1 provirus was correlated with transcriptional activation from HIV-1 LTR (5, 6, 11), whereas hypoacetylation mediated by HDAC was correlated with its repression (12)(13)(14)(15)(16). For example, we reported that AP-4 acts as a transcriptional repressor by recruiting HDAC molecules and is involved in the maintenance of viral latency (14).…”
Section: Reactivation Of Latent Hiv-1 Infection By the Periodontopathmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, class 1 HDACs are recruited to the proviral DNA, in proximity to nuc-1, through the action of DNA binding proteins. Nuclear factor (NF)-κB p50 homodimer, activating enhancer binding protein 4 (AP-4), retinoblastoma-family protein 2 (RBF2), as well as c-Myc and specificity protein 1 (SP-1) recruit class I HDACs to the LTR, which in turn results in deacetylation of local histones, compaction of the chromatin and prevention of RNA polymerase II binding (25,(27)(28)(29)(30)(31).…”
Section: Which Hdac Is Best For Hiv-1 Expression?mentioning
confidence: 99%
“…Margolis and colleagues demonstrated that the transcription factor YY1 can act as a repressor of HIV transcription by recruiting HDAC-1 to the provirus (11). Later studies demonstrated that nuclear factor (NF)-κB p50 homodimers (12), AP-4 (13), CTIP2 (14), Sp1 and c-Myc (15), and CBF-1 (16) can participate in HDAC-1 recruitment. HDAC-2 and -3 can also associate with the HIV long terminal repeat (LTR), and play a role in the repression of LTR expression (14,17).…”
Section: Introductionmentioning
confidence: 99%